The Role of Media-Based Public Awareness in Preventing Irregular Migration (Salam International Academic Journal, 2025)
This study aims to examine the constructive role of media-driven public awareness in the prevention of irregular migration. It is qualitative research conducted using the focus group method with seven senior faculty members from the Faculty of Journalism at Nangarhar University. The collected data were analyzed using thematic analysis.The findings indicate that although the credibility of mass media is generally high, the credibility of social media varies significantly. A considerable number of individuals inclined toward irregular migration rely on social media as their primary source of information. Likewise, human traffickers exploit social media platforms to persuade young people to migrate through illegal channels for financial gain.Despite this, social media has also been identified as an effective tool in anti-migration awareness campaigns. News genres and audio-visual spots are considered among the most effective formats for delivering media content. Thus, the media is not only a means of disseminating information but also plays a critical role in shaping public opinion, influencing beliefs, and guiding decision-making processes.If utilized strategically and responsibly, media can serve as a powerful instrument in preventing irregular migration. This study recommends the production of evidence-based and high-quality content to support future media interventions in this domain.
Keywords: Visual messages; social media; audio messages; migration; media campaign; media-based public awareness; irregular migration